A new type of triboelectric nanogenerator with self-actuated series-to-parallel electrical interface based on self-synchronized mechanical switches for exponential charge accumulation in a capacitor. (August 2019) - Ben Ouanes, M.A.; Samaali, H.; Galayko, D.; Basset, P.; Najar, F.
Abstract: We present a new concept for impact-based triboelectric nanogenerators (TENG) inspired from the electrostatic machines of the 18th century. With this system, the electrical energy converted from the mechanical domain is automatically accumulated in a large capacitance without the need of diodes. Our TENG has three electrodes and self-synchronized/self-actuated mechanical switches, which automatically and repeatedly connect the capacitances of the system according to their series and parallel configurations in order to reproduce a behaviour similar to the Bennet's charge doubler. The movable and freestanding electrode is covered with triboelectric patches that drastically decreases the start-up time. The output voltage, and so the harvested energy, increases exponentially until either the output voltage reaches the air dielectric breakdown or a saturation occurs because the electrostatic forces become comparable to the mechanical ones. We have developed a complete numerical model that takes into account both electrical and mechanical forces and is able to show the saturation phenomena due to the high electromechanical coupling occurring at high voltage. This model has been validated with practical experiments where the prototype were excited with a sinusoidal acceleration of 0.2 g rms at 5 Hz. This new and diode-free concept can be applied to any TENG having at least one variable capacitor to boost the mechanical-to-electrical energy conversion. Graphical abstract: We report a new type of triboelectric nanogenerator (TENG) having alternating and self-actuated series-to-parallel interfaces based on self-synchronized mechanical switches. It has been inspired from the Bennet doubler electrical machine. The TENG is composed of a freestanding electrode, two anti-phase variable capacitors excited by the external vibrations, and a reservoir capacitor. The absence of diodes and their unavoidable voltage threshold for signal rectification, combined with the boost introduced by the Bennet-like doubler structure, can largely improve the energy conversion efficiency of TENGs, especially during the start-up.Image 1 Highlights: We report a new TENG having a self-actuated series-to-parallel electrical interface based on mechanical switches. The absence of diodes combined with the Bennet-like doubler can largely improve the energy conversion efficiency of TENGs. A numerical model that takes into account both electrical and mechanical forces has been validated with the experiments.